Professional learning and TVET: challenges and perspectives for teachers and instructors - Harteis, Christian (International handbook of education for the changing World of Work)

Lernen von Lehrenden im Arbeitsprozess - Mulder, Regina H; Harteis, Christian; Gruber, Hans (Lehrprofessionalität - Bedingungen, Genese, Wirkungen und Messung)

Wirtschaft und Betrieb - Heid, Helmut; Harteis, Christian (Handbuch Bildungsforschung)

Teacher Collaboration Concerning ICT-Use and its Essential Conditions - Schulz-Zander, Renate; Eickelmann, Birgit (Proceedings – 9th WCCE. IFIP World Conference on Computers in Education)

E-teaching plus. Die webbasierte Lernumgebung für situiertes Lernen mit Unterrichtsvideos - Schulz-Zander, Renate; Eickelmann, Birgit

National Policies and Practices on ICT in Education: Germany - Schulz-Zander, Renate; Eickelmann, Birgit (Cross-national Information and Communication Technology. Policies and Practices in Education)

Erfolgreich Computer und Internet in Grundschulen integrieren – eine empirische Analyse aus Sicht der Schulentwicklungsforschung - Eickelmann, Birgit; Schulz-Zander, Renate; Gerick, Julia (Europäisierung der Bildung - Konsequenzen und Herausforderungen für die Grundschulpädagogik)

Rezension zu L.J. Issing & P. Klimsa (Hrsg.) (2009). Online-Lernen. Handbuch für Wissenschaft und Praxis. München: Oldenbourg Verlag - Eickelmann, Birgit (Journal for Educational Research Online)

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Language and Logic in German Post-Hegelian Philosophy - Peckhaus, Volker (The Baltic International Yearbook of Cognition, Logic and Communication, Bd. 4: 200 Years of Analytical Philosophy)

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Die Welterbeliste - zwischen Kanonbildung und Kanonverschiebung - Seng, Eva- Maria
Demnächst in: ZS ejournal Kunstgeschichte, LMU München. Open Peer Reviewed Journal www.kunstgeschichte-ejournal.net

Arno Eugen Fritsche - Seng, Eva- Maria (Protestantische Profile im Ruhrgebiet. 500 Lebensbilder aus 5 Jahrhunderten)

Denkmalpflege und kulturelles Erbe - Seng, Eva- Maria (MUT. Forum für Kultur, Politik und Geschichte)

Elias Holl - Seng, Eva- Maria (Killy-Literaturlexikon (Neuauftritt), München, Berlin)

„Aufgabe, Wirken, Möglichkeiten: 150 Jahre Kirche und Kunst in Württemberg“ - Seng, Eva- Maria (Blätter für württembergische Kirchengeschichte)